Optimization of tilt angle for solar panel: Case study Tunisia - Hatem Tlijani; Abir Aissaoui; Rached Ben Younes (Institute of Advanced Engineering and Science, 2017)
This paper is a comparisation study between an experimental data and Matlab simulation of output PV characteristic affected by the orientation and the tilt angle of a photovoltaic solar module with inclined plane and by the dimension of the panel. The PV panel was rotated towards the east, south and west and positioned for the angles 0°, 30°, 45°, 60° and 90°. In this position, the values of current, voltage and power are measured. In the other side, using the mathematical model to calculate the solar radiation incident on an inclined surface as a function of the tilt angle was developed in MATLAB/SIMULINK model. The optimum angles were determined as positions in which maximum values of solar irradiation and maximum power were registered to characterize the P-V and V-I photovoltaic panel.